Genome-wide identification, phylogenetic investigation and abiotic stress responses analysis of the PP2C gene family in litchi (Litchi chinensis Sonn.) - Yang, Jie; Chen, Rong; Liu, Wei; Fan, Chao (Frontiers in Plant Science, 2025)
As an important regulatory protein phosphatase in the abscisic acid (ABA) signal transduction pathway and mitogen-activated protein kinases (MAPK) cascade, type-2C protein phosphatase (PP2C) plays crucial roles in plant responses to abiotic stresses. However, the PP2C gene family’s responses to abiotic stress in litchi (Litchi chinensis Sonn.) have not been systematically studied. In this study, we predicted the 68 PP2C (designated LcPP2C) genes randomly distributed across fourteen chromosomes in the litchi genome. Phylogenetic tree analysis among litchi, Arabidopsis (Arabidopsis thaliana), and rice (Oryza sativa) revealed that the phylogenetic tree was divided into thirteen groups (A, B, C, D, E, F1, F2, G, H, I, J, K, and L). Closely linked LcPP2C genes within the same group exhibited various similarities in gene structures and motif compositions. Collinearity analysis demonstrated that segmental duplication (SD) events were the main dramatically increasing numbers in the LcPP2C gene family members. Cis-acting element analysis revealed that the 68 LcPP2C genes contained hormone and stress response elements with varying quantities, implying their potential in litchi stress resistance. Expression analysis showed that all the LcPP2C genes exhibited varying expression levels across nine different litchi tissues, more than 50% of genes within each group displayed similar tissue-specific expression patterns. The expression intensity, duration and regulation direction (up- or down-regulation) of the LcPP2C genes were varied under different abiotic stresses (cold, heat, and drought). The physiological and biochemical tests indicated that eight activation indexes (peroxidase (POD), catalase (CAT), superoxide dismutase (SOD), malondialdehyde (MDA), proline (PRO), soluble protein (SP), hydrogen peroxide (H2O2), and soluble sugar (SS)) increase at different level. Additionally, we analyzed physicochemical properties, subcellular locations, and secondary structures of the LcPP2C family members. Notably, the extensive connectivity of LcPP2C32/60/9/37 underscored their vital roles in orchestrating and regulating biomolecular networks. These results provide valuable information for the identification of the LcPP2C genes and ideas for the cultivation of its transgenic induction lines in litchi.